BF3·Et2O Catalysed 4-Aryl-3-phenyl-benzopyrones, Pro-SERMs, and Their Characterization - Ambika Srivastava; Pooja Singh; Rajesh Kumar (Advances in Pharmacological Sciences)
We have synthesized the novel 4-(4-hydroxy-benzyl)-3-phenyl-chromen-2-one which is a precursor of SERMs with a smaller number of steps and good yield. Two methodologies for the synthesis have been worked out. Anhydrous BF3·Et2O catalyzed reaction was found to be selective for product formation while anhydrous AlCl3, FeCl3, and SnCl4 catalyzed ones were nonselective.